A spiritual intelligence model in National Philosophy of Education: an Islamic perspective - Tengku Abdul Aziz, Tengku Mohd Farid; Zakaria, Shahsuzan; Ahmad Bukhari, Nurul Iman; Zakaria, Razimi; Mat Zin, Mohd Nazri (Universiti Teknologi MARA, Kelantan, 2018)
One of the underlying principles of the Malaysia National Philosophy of Education (NPE) is to produce well-balanced human capital in terms of physical, intellectual, emotional and spiritual aspects. However, of all human intelligences, the concept of spiritual intelligence is not widely discussed especially in the educational context. In this diverse world of complex cultural and religious composition, the spiritual elements in NPE are being separated and narrowed down to religious and moral studies. In the wake of all issues regarding morality and ethics pertaining to the Malaysian educational system, the aspect of spiritual intelligence cannot be further neglected. The challenge for Muslims, especially in the era of Industrial Revolution 4.0, is to have further interpretation from a new fresh outlook within the Islamic spiritual intelligence perspective. Thus, the study proposes an Integrated Islamic Spiritual Intelligence model in accordance to the Malaysia National Philosophy of Education with the aim to provide an integrated view on Islamic Spiritual Intelligence (ISI). It is expected that this model becomes a foundation for educators to complement teaching principles and beliefs, subsequently reflecting this in teaching enrichment. In the long run, this integration seeks to produce a more holistic Muslim generation, who not only aims for worldly success, rather ultimate success in the Hereafter.